Principles of Mahomedan law - Mulla, Dinshah Fardunji (Gurgaon, 2017)
Principles of Mahomedan Law by Dinshaw Fardunji Mulla is the most authoritative, well-acknowledged and comprehensive commentary on the subject. This legal classic has withstood the test of time and served the legal profession and everyone associated with it, for over a century. Its appeal has not withered but has only grown with the passage of time. Widely quoted in judgments of the Supreme Court as well as various High Courts, this classic work has been relied on and quoted by the Constitutional Bench of the Supreme Court in its recent judgement on the validity of Triple Talaq. <b r><b r>In the month of May 2017, a constitutional Bench was constituted to decide on the controversial subject of constitutionality of the practice of divorce through Triple Talaq. This judgement delivered on 22 Aug 2017, will have far reaching effects on not only the lives of Muslim women, but also on the role that the Supreme Court and Parliament can play in bringing reforms to personal Laws. <b r><b r>Salient Features:-<b r>? Highly acclaimed and most authoritative commentary on the subject<b r>? Illustrates and explains the provisions of Mahomedan law in a lucid, comprehensive and systematic manner<b r>? Covers all aspects and dimensions of Islamic law in India<b r>? Provides lucid explanation of complexities, background, history and sources apart from the extant law<b r>? Covers the latest case law including the landmark triple talaq judgment<b r>? An extensive introduction provides useful information about the basic sources of law and provides a starting point for future studies
Keywords: Islamic law